2003
DOI: 10.1103/physrevb.67.104426
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of the critical temperature for the planar rotator model with nonmagnetic impurities

Abstract: We performed Monte Carlo simulations to calculate the Berezinskii-Kosterlitz-Thouless (BKT) temperature TBKT for the two-dimensional planar rotator model in the presence of nonmagnetic impurity concentration (ρ). As expected, our calculation shows that the BKT temperature decreases as the spin vacancies increase. There is a critical dilution ρc ≈ 0.3 at which TBKT = 0. The effective interaction between a vortex-antivortex pair and a static nonmagnetic impurity is studied analytically. A simple phenomenological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 15 publications
7
43
1
Order By: Relevance
“…However, for d = 2 regular lattices, the percolation threshold (the density of vacancies required to disconnect the lattice) is ρ ≈ 0.41. Thus the work of [36] suggests that, indeed, the critical temperature vanishes before the percolation threshold is reached. In a later study, however, Berche et al suggested that the critical site-density is closer to the percolation threshold [37].…”
Section: The Diluted Xy Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for d = 2 regular lattices, the percolation threshold (the density of vacancies required to disconnect the lattice) is ρ ≈ 0.41. Thus the work of [36] suggests that, indeed, the critical temperature vanishes before the percolation threshold is reached. In a later study, however, Berche et al suggested that the critical site-density is closer to the percolation threshold [37].…”
Section: The Diluted Xy Modelmentioning
confidence: 99%
“…This issue is addressed in [35][36][37][38]. According to the Harris criterion, disorder does not change the leading scaling behaviour of a model if the critical exponent α associated with the specific heat of the pure model is negative [39].…”
Section: The Diluted Xy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found (ρ − ρ percolation ) ν , with ν = 1.56024. More recently Leonel et al [21] obtained the phase diagram T BKT × p for the site diluted model. Here, p is the density of magnetic sites.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] had studied the effects of nonmagnetic impurities on the KT transition. Since nonmagnetic impurities can be viewed as lattice vacancies, the results found that the KT transition disappears as the vacancy density reaches the lattice percolation limit.…”
Section: Introductionmentioning
confidence: 99%